Predictors of prediabetes/diabetes and hypertension in Ethiopia: Reanalysis of the 2015 NCD STEPS survey using causal path diagrams - Norris, Tom; Genye, Tirsit; Girma, Meron; Hussen, Alemayehu; Pradeilles, Rebecca; Bekele, Zerihun; Van Zyl, Cornelia; Samuel, Aregash (Wiley, 2024)
The objective of our study was to reanalyse the Ethiopia STEPwise approach to Surveillance Noncommunicable Disease Risk Factors survey (NCD STEPS), using causal path diagrams constructed using expert subject matter knowledge in conjunction with graphical model theory to map the underlying causal network of modifiable factors associated with prediabetes/diabetes and hypertension. We used data from the 2015 Ethiopia NCD STEPS representative cross-sectional survey (males; n = 3977 and females; n = 5823 aged 15–69 years) and performed directed acyclic graph-informed logistic regression analyses. In both sexes, a 1-unit higher in body mass index (BMI) and waist circumference (WC) were positively associated with prediabetes/diabetes (BMI: males: adjusted odds ratio [aOR]: 1.07 [95% confidence interval: 1.0, 1.1], females aOR: 1.03 [1.0, 1.1]; WC: males: aOR: 1.1 [0.9, 1.2], females: aOR: 1.2 [1.1, 1.3]) and hypertension (BMI: males: aOR: 1.2 [1.1, 1.2], females aOR: 1.1 [1.0, 1.1]; WC: males: aOR: 1.6 [1.4, 1.8], females: aOR: 1.3 [1.2, 1.5]). Although residing in urban settings was associated with higher odds of hypertension in both males (aOR: 1.79 [1.49, 2.16]) and females (aOR: 1.70 [1.49, 1.95]), it was only associated with prediabetes/diabetes in males (aOR: 1.56 [1.25, 1.96]). Males and females in pastoralist areas had lower odds of prediabetes/diabetes compared with their agrarian counterparts (males: aOR: 0.27 [0.14, 0.52], females: aOR: 0.31 [0.16, 0.58]). Physical activity was associated with lower odds of prediabetes/diabetes among females (aOR: 0.75 [0.58, 0.97]). Other diet-related modifiable factors such as consumption of fruit and vegetable, alcohol or salt were not associated with either prediabetes/diabetes or hypertension. Our findings highlight the need to implement interventions that prevent overweight/obesity and nutrition-related NCDs, particularly in urban areas.